2017
DOI: 10.1016/j.najef.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Does US news impact Asian emerging markets? Evidence from nonparametric causality-in-quantiles test

Abstract: This paper aims to analyse whether US news on inflation and unemployment causes returns and volatility of seven emerging Asian stock markets from 1994 to 2014, by employing the causalityin-quantile approach. We find evidence that US news affect returns and/or volatility of all the seven stock markets considered, with these effects clustered around the tails of the conditional distribution of returns and volatility when they are either in bear or bull modes. In general, our results highlight the importance of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Al-Shami and Ibrahim (2013) reported contradictory results in case of Kuwait, where an increase in inflation leads to an increase in stock prices after one month, and a decrease in stock prices after two months. Stock markets may also be sensitive to inflationary factors in overseas countries; for instance, Balcilar et al (2017) found that during the period 1994 -2014, Asian stock prices were impacted by news about US inflation.…”
Section: Inflationmentioning
confidence: 99%
“…Al-Shami and Ibrahim (2013) reported contradictory results in case of Kuwait, where an increase in inflation leads to an increase in stock prices after one month, and a decrease in stock prices after two months. Stock markets may also be sensitive to inflationary factors in overseas countries; for instance, Balcilar et al (2017) found that during the period 1994 -2014, Asian stock prices were impacted by news about US inflation.…”
Section: Inflationmentioning
confidence: 99%
“… 11 The discussion and notation contained in this section follows Balcilar et al (2017a , 2017b , 2017c , 2017d ). …”
mentioning
confidence: 99%
“…However recent studies, borrowing from the literature on financial markets (see for example, Balcilar et al, (2017a) and Marfatia et al, (2017)), have identified monetary policy surprises on monetary policy committee (MPC) meeting dates from high-frequency (intraday and daily) data, as a possible predictor for commodity markets in general, which in turn has witnessed tremendous financialization in the recent years . Using regression-based methods studies have analyzed the impact of such shocks (Hayo et al, 2012;Rosa, 2014;Basistha and Kurov, 2015;Chebbi, 2018a, b;Gospodinov and Jamali, 2018;Kurov and Stan, 2018), along with macroeconomic news surprises (Kilian and Vega, 2011;Chatrath et al, 2012, Bahloul and on oil returns and volatility.…”
Section: Introductionmentioning
confidence: 99%